The Orbiniidae (Annelida: Polychaeta) of the BIOSHELF Project, Andaman Sea, Thailand. - Eibye-Jacobsen, Danny (Phuket Marine Biological Center Special Publication, 2002)
A total of 176 specimens of Orbiniidae are reported from the collections made during the Thai–Danish BIOSHELF Project in 1996–97 in the Thai sector of the Andaman Sea. Twelve species (seven named) are reported from this material, of which Leitoscoloplos mackiei, L. papillatus, Scoloplos (Leodamas) brevithorax and S. (Scoloplos) pseudosimplex are newly described. The diagnosis of Leitoscoloplos Day, 1977 is slightly emended. A member of the genus Pettibonella Solís-Weiss and Fauchald, 1989 is reported for the first time since its original description. SEM photographs are provided for eight species.
World Polychaeta Database (WPolyD)